A MOF-membrane based on the covalent bonding driven assembly of a NMOF with an organic oligomer and its application in membrane reactors. Issue 93 (3rd October 2016) - Jiang, Wei-Ling; Ding, Luo-Gang; Yao, Bing-Jian; Wang, Jian-Cheng; Chen, Gong-Jun; Li, Yan-An; Ma, Jian-Ping; Ji, Jun; Dong, Ying; Dong, Yu-Bin
Abstract : Fabrication of a covalent bonding driven UiO-66-MOF-based membrane, which is generated from the self-assembly of NMOFs with organic oligomer SBUs, and its application in membrane reactors are reported. Abstract : A UiO-66-MOF-based membrane UiO-66-TEM (1 ) was prepared by the assembly of methacrylamide-decorated UiO-66-NH-Met with a thiol side chain-attached polysiloxane (PSI-SH) via a photoinduced thiol–ene click reaction. The obtained membrane1 can be a platform to support Au nanoparticles (Au NPs) to generate an Au–MOF–polymer composite membrane Au@UiO-66-TEM (2 ).1 and2 can be used to build highly efficient continuous flow-through membrane reactors for Knoevenagel condensation of 4-nitrobenzaldehyde with malononitrile and 4-nitrophenol (4-NP) reduction at ambient temperature, respectively.